2010
DOI: 10.1111/j.1600-0447.2010.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

10‐Year trends in the treatment and outcomes of patients with first‐episode schizophrenia

Abstract: Nielsen J, le Quach P, Emborg C, Foldager L, Correll CU. 10‐Year trends in the treatment and outcomes of patients with first‐episode schizophrenia. Objective:  The first episode of schizophrenia is a critical period for illness course and outcomes. We aimed to investigate treatments and outcomes during the first year after the diagnosis of schizophrenia. Method:  Pharmacoepidemiologic inception cohort study of all newly diagnosed patients with schizophrenia in Denmark (n = 13 600) 1996–2005. Results:  From 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
7
63
0
Order By: Relevance
“…Antipsychotic polypharmacy was defined as treatment with at least two antipsychotics during a four month period (i.e., at least two renewals of each antipsychotic prescription). This definition, which has been employed previously (Nielsen et al, 2010b), was used in order to exclude patients switching antipsychotic medication by the cross-tapering method. The four-month period was chosen, as the largest pack size, i.e., 100 tablets, would have been used within that period.…”
Section: Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Antipsychotic polypharmacy was defined as treatment with at least two antipsychotics during a four month period (i.e., at least two renewals of each antipsychotic prescription). This definition, which has been employed previously (Nielsen et al, 2010b), was used in order to exclude patients switching antipsychotic medication by the cross-tapering method. The four-month period was chosen, as the largest pack size, i.e., 100 tablets, would have been used within that period.…”
Section: Exposurementioning
confidence: 99%
“…Despite this, several studies have shown that around 20% of patients with schizophrenia are treated with APP (Gallego et al, 2012a;Kim et al, 2014;Nielsen et al, 2010b). Moreover, prior studies have indicated that APP is related to greater illness severity and chronicity, psychiatric comorbidity and that there are substantial variations across centers, countries, time periods and populations (Gallego et al, 2012b).…”
Section: Introductionmentioning
confidence: 96%
“…Never say never to polypharmacy ⁄ combinations Rank and file psychiatrists seem to have ignored the call for Ôalways say monotherapyÕ as the data show that antipsychotic polypharmacy ⁄ combination use is growing and is higher than ever, overtaking monotherapy (11), and seemingly impervious to educational and administrative interventions to reduce polypharmacy (12,17). Although some believe these trends reflect substandard care, the shift toward more antipsychotic polypharmacy ⁄ combinations may actually be due to something else, namely, the growing gap between evidence-based practice and practicebased evidence, at least for certain patient populations receiving antipsychotics.…”
mentioning
confidence: 99%
“…Other contributing factors appear to be lack of opportunity for employment and work, leading to lack of satisfaction, stigma and being seen as a burden on the family, at least in a few cases [46]. However persistence of symptoms, suicidality, limited functioning, inability for independent living, and inability to resume work in large number of patients does bring out limited success with contemporary therapy [47]. In another study which compared rates hospitalization between 1994 and 2004, authors highlighted admission rates of 50% and 85% on first generation antipsychotic drugs and 51 and 81% on second generation antipsychotic drugs respectively.…”
Section: Outcomes In Schizophrenia and Resiliencementioning
confidence: 99%